Characteristics, behaviors, and teaching tools that promoted online learning among university students during COVID-19 - Torres, Gerardo (2021)
The purpose of this research was to identify the characteristics, behaviors, and teaching tools that, according to the students of a degree in human resources from western Mexico, promoted learning during online classes due to COVID-19. The research was qualitative, non-experimental, exploratory, and cross-sectional. An open-ended questionnaire was applied to 109 participants (78% women and 22% men; average age 22.6 years). As a result, the teaching staff that promotes learning is characterized by being explanatory, understanding, patient, dynamic and empathetic; In behavioral terms, he explains the topics, schedules practical activities, gives constant feedback, sets flexible tasks, and is available to the student when required. In addition, the most effective teaching tools were videos, slides, video calls, virtual classrooms, and digital repositories.